Leaf anatomy of the species of Panicum L. subg. Panicum (Poaceae: Panicoideae: Paniceae) from Brazil - Guglieri, Adriana (2008)
An analysis of the leaf anatomy of the thirty species of Panicum L. subg. Panicum occurring in Brazil was performed, aiming to find useful characters for their identification. Midblade transverse sections were conducted using a microtome and dyed with Blue Toluidine. Transverse sections were viewed with an Olympus CH30 microscope and photographs were taken using an Olympus PM-C35B camera. The anatomical characters with higher taxonomic value are: presence and depth of furrows on adaxial surface of the epidermis; presence and distribution of papillae on epidermical cells; presence and type of columns of colorless cells in the mesophyll; and relative size of bundle sheath´s parenchymatic cells on second order bundles, and if the size is not uniform, the shape of their adaxial cells. The results indicated that leaf anatomy characters are more useful for the delimitation of the sections of Panicum subg. Panicum, although differentiating some of the studied species.